Beyond Recitation: Integrating the Turjuman Method for Qur'anic Comprehension in Madrasah Education - Endarwati, Rulik; Abshor, Ulil (Tadibia Islamika: Journal of Holistic Islamic Education, 2025)
This study examines the implementation of the Turjuman method in teaching Qur'anic comprehension at MIN 1 Madiun. The Turjuman method employs a word-by-word translation approach accompanied by basic grammatical analysis to address students' limited proficiency in Arabic and enhance their understanding of Qur'anic texts. Utilizing a qualitative case study design, data were collected through classroom observations, semi-structured interviews with teachers and students, and document analysis of instructional materials and student assessments. The findings reveal that the Turjuman method significantly improves students' comprehension of Qur'anic structure and meaning while fostering awareness of moral and spiritual values applicable to daily life. Students demonstrated positive responses, evidenced by increased motivation, active classroom engagement, and the development of Islamic character traits. Despite implementation challenges—including limited instructional time, varying levels of teacher preparedness, and insufficient supporting materials—the Turjuman method proves effective and relevant for Qur'anic pedagogy. This study recommends broader adoption of the method as an integrative and contextual learning strategy in madrasah curricula, with implications for curriculum development and teacher professional training in Islamic elementary education.